STABILITAS DAN KUALITAS DALAM MENYELESAIKAN TUGAS SEBAGAI TANGGUNG JAWAB DI KALANGAN MAHASISWA SEKOLAH TINGGI TEOLOGI - Dewi Astuti; Saleleubaja, Junardi; Martina Novalina (International Forum of Researchers and Lecturers, 2024)
Based on the results of this study, researchers found many factors and habits of students in the field, students feel burdened in completing assignments as a responsibility, students view the task as a heavy burden in doing the task as the responsibility of a student. Whereas students who have an academic attitude should, the more tasks, the more students work hard to add insight into doing tasks as the responsibility of an academic student. As for this research method, the researcher uses a qualitative research method with a library research approach. As for the findings of this study, researchers found that many students of the Ecumenical Theological College of Jakarta delayed in completing assignments as a responsibility that must be done optimally. After conducting research, researchers found many factors that hinder students in completing assignments, namely: playing games, playing social media, piling up tasks, difficulty finding references, easy sleepiness, no one motivates and hanging out with friends discussing something that is not important, so that the time to do the task is limited. The strategies that researchers can list to improve the stability and quality of motivation in completing assignments as the responsibility of students of the Ecumenical Theological College Jakarta include: Students make a priori scale.